Forecasting trend output in the Euro area - Christian Schumacher (Hamburg Institute of International Economics (HWWA), 2000)
This paper estimates and forecasts trend output and output gaps for the Euro area. In the monetary strategy of the European Central Bank (ECB), trend output is used to forecast a reference value for money. For this purpose, trend output must be forecasted as well. In this paper, a permanent-transitory decomposition (PT) based on cointegration restrictions gives an estimate of trend output in the Euro area. Ex-ante forecasts of trend output are generated and to get an impression of the forecast uncertainty, bootstrap simulation is employed to construct prediction intervals that take into consideration estimation uncertainty. The empirical uncertainty around trend output is relatively smaller than the uncertainty of the output gap. The absolute uncertainty of both indicators is quite large and questions their usefulness for monetary policy. When relying on such indicators monetary authorities should clarify this uncertainty.
Keywords: 330; Konjunkturprognose; Prognoseverfahren; Zeitreihenanalyse; Schätzung; Theorie; EU-Staaten